THREE DIMENSIONAL IMAGE ANALYSIS OF MINOR SALIVARY GLANDS IN 180-DAY RATS BORN WITH MACROSOMIA - Garmash, Olga (Medicinski časopis, 2018)
The objective of this study is to determine the morphometric differences in the minor buccal salivary glands in rats aged 6 month with fetal macrosomia (groups under study) and in rats aged 6 month after a normal intrauterine development (control group) by using a 3-D analysis technique. Methods. The fetal macrosomia was induced in the four different ways. To apply the morphological analysis, the tissues of oral cavity mucosa of six-month-old rats were used. The 3-D images acquired by confocal microscopy were used for estimating the morphometrical characteristics of minor buccal salivary gland microscopic structures. Results. On reaching the age of six-month, the descendants of the rats in all macrosomic groups have the average body weight, the average body length, and the average weight-to-length ratio comparable to those in the Control Group. In rats born with different fetal macrosomia modeling, when the age of 6 months was reached, the deviations in the Groups under study from the Control Group were found to appear to various degree in the following parameters: the acinus area, the acinus gap area, the number of mucous acinar cells in the acinus, the height of the cytoplasm of mucous acinar cells, and the percentage fractions of the relative area of mucous acinar cells cross-sections, area of acinar gap cross-sections and relative area of glandular stroma. Conclusion. The clustered technique assessment of these deviations brings us to the conclusion about the presence of hypoplasia of minor buccal salivary glands in rats born with fetal macrosomia.